Reimagining academic identities in response to research demands at Universities of Technology - Gumbi, Thobani; McKenna, Sioux (Critical Studies in Teaching and Learning, 2023)
In the last volume of this journal, Garraway and Winberg called for a reimagination of Universities of Technology (UoT) within the South African higher education system. This article continues that conversation by looking at the implications that the formation of the Out had for academics’ identities. Technikon lecturers’ identities were closely tied to workplace expertise but demands for research in Out shave changed this. A social realist analysis of interviews with fifteen academics at three UoTs finds that research remains a contested issue. Interviewees understood research to take the form of acquiring postgraduate qualifications, rather than as an ongoing activity tied to their identities. Echoing Garraway and Winberg’s study, the bureaucratic nature of the institutional culture was referred to as a constraint. There was also a view that for this programme, Dental Technology, a demand for research was needed from industry if this was to be a valued aspect of academics’ identities.